2013
DOI: 10.7567/jjap.52.055501
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Isoelectronic Te Doping on the Physical Properties of ZnO Films Grown by Molecular-Beam Epitaxy

Abstract: In molecular-beam epitaxy, isoelectronic Te doping induces the serious change of the physical properties of ZnO films: i) Incorporated Te concentration is proportional to the 2.2th power of injected Te flux in the logarithmic scale; ii) Te-doped ZnO lattices are dominated by the relaxation mechanism of compressive strain; iii) incorporated Te atoms substitute to the O sites of ZnO lattices; iv) the low-level injection of Te atoms below $10 19 cm À3 improves the crystalline quality in the ZnO films; and v) isoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…This type of substitution with less electronegative anions raises the valence band energy with respect to the vacuum level, thus reduces the activation energy of acceptors as well as compensation effects due to spontaneous formation of native defects . Reports are scarce on Te‐doped ZnO in the literature particularly its location in the lattice and the associated optical band gaps . Te has valence electronic configuration 5s2 5p4 and is known to exhibit ambipolar behavior, e.g., TeO 2 (Te charge state is +4) and ZnTe (Te charge state is −2).…”
Section: Introductionmentioning
confidence: 99%
“…This type of substitution with less electronegative anions raises the valence band energy with respect to the vacuum level, thus reduces the activation energy of acceptors as well as compensation effects due to spontaneous formation of native defects . Reports are scarce on Te‐doped ZnO in the literature particularly its location in the lattice and the associated optical band gaps . Te has valence electronic configuration 5s2 5p4 and is known to exhibit ambipolar behavior, e.g., TeO 2 (Te charge state is +4) and ZnTe (Te charge state is −2).…”
Section: Introductionmentioning
confidence: 99%
“…and (112) within 32° to 37° and 48° and 67° respectively while for Al-doped, intense peaks were identified along (100), (002) and (101) at 2θ = 36.24, 32.37 and 36.24° respectively. Generally it was seen that irrespective of annealing growth technique and doping not withstanding doping element used, ZnO has high diffraction peaks elaborated at (100) and (002) in all cases This observation indicated that ZnO thin film is strongly c-axis oriented with wurtizite structural characteristic, although increase in the percent of doping element affects and often shifts the diffraction peak slightly to a lower angle side with report that crystal structure of the film deteriorate at a higher doping concentration of doping element as it decreases the c-lattice [10,13,25].…”
Section: Structural Analysismentioning
confidence: 77%
“…The flexibility of the its heterostructures has been found to lead to expanded possibility of its device functionalities to various kind of application apart from solar energy devices. Uniquely apart from its easy realization of bipolar based devices due to doping symmetry issue which characterizes other II-IV semiconductors that can be readily doped n-type, it has been found very difficult to reproduce the ZnO doped p-type semiconductor because of lack of dopants having shallow acceptor level as a result of low dopant stability [10]. The dopants also affects in a strong term the microstructural, electrical and optical characteristics of the thin film [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the Se-doped ZnO photocatalyst effectively inhibited the recombination of photogenerated electrons and holes, and the photocatalytic degradation performance was remarkably improved. Park et al [16] investigated the effect of isoelectronic Te doping on the physical properties of ZnO by molecular epitaxy. The results showed that the implantation of Te atoms narrowed the emission line and suppressed the deep energy level, which is beneficial to improve the crystallinity.…”
Section: Introductionmentioning
confidence: 99%